2010
DOI: 10.3814/2010/725381
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing Subsurface Drip Irrigation and Conservation Tillage in Cotton Production Systems

Abstract: Ground water resources for irrigated agriculture are becoming increasing limited in semiarid regions of the world. Subsurface drip irrigation (SDI) and a no-till conservation tillage system were evaluated over 3 years on cotton (Gossypium hirsutum, L.) production and fiber quality in north Texas. Subsurface drip irrigation significantly increased cotton yields over that from furrow irrigation in 2 of 3 yr. When averaged over 3 yr, the cover crop treatments on 1 and 2 m drip line spacing and a 100% ET replaceme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…In five of the seven studies, SDI had at least some benefit in cotton production, and in two studies it did not. Stated SDI benefits varied between studies but included yield increases (Sij et al, 2010;Lamm, 2016;Barnes et al, 2020;Sorensen et al, 2020), reduction in greenhouse gas (GHG) emissions (Bronson et al, 2018), and greater profitability (Sij et al, 2010). Negative responses attributed to SDI included a reduction in small rainfall event utilization (Goebel and Lascano, 2019) and a greater incidence of spider mite damage (Hollingsworth et al, 2014).…”
Section: Sdi In Comparison To Alternative Irrigation Systems For Cotton Productionmentioning
confidence: 99%
“…In five of the seven studies, SDI had at least some benefit in cotton production, and in two studies it did not. Stated SDI benefits varied between studies but included yield increases (Sij et al, 2010;Lamm, 2016;Barnes et al, 2020;Sorensen et al, 2020), reduction in greenhouse gas (GHG) emissions (Bronson et al, 2018), and greater profitability (Sij et al, 2010). Negative responses attributed to SDI included a reduction in small rainfall event utilization (Goebel and Lascano, 2019) and a greater incidence of spider mite damage (Hollingsworth et al, 2014).…”
Section: Sdi In Comparison To Alternative Irrigation Systems For Cotton Productionmentioning
confidence: 99%
“…[226]. These can range from a small-scale subsistent farming (e.g., in water deficient areas of the developing world where subsurface irrigation tape can be connected to a water bucket for uniform delivery of water and nutrients to the crop root zone) through large scale subsurface irrigation practices already in use (e.g., in the production of cotton-in [227] and [228]) to futuristic, sophisticated "smart field" systems that will allow for precise micro-delivery of inputs into the plant root zone based on the availability of real-time soil data (such as moisture, mineral/organic nutrient, oxygen, carbon dioxide, N 2 O and ethylene content, pH, and potentially others) collected with sensor nodes that provide information on the biology of the air (aerial movement of pathogens), soil (microbial community dynamics) and plant (developmental stage, nutrition and health status). Progress in sensor technology, data transmission, their collection and processing capacity, and development of inexpensive next generation DNA sequencing technologies [229] that can deliver fast results on microbial population dynamics in the field will determine the speed, and the level of precision with which we can conduct research and create frugal input management practices that enhance soil, plant, and potentially, human health.…”
Section: Discussionmentioning
confidence: 99%
“…These data are consistent with other research using SSDI. Yield data from Texas (Sij et al, 2010) showed that conventionally tilled cotton had the same yield as with no‐tilled cotton (cotton planted in rye) two out of three years. The three‐year average showed no difference between conventional and no‐till systems when irrigated using SSDI with laterals spaced 3.2‐ or 6.5‐ft distances (Sij et al, 2010).…”
Section: Crop Yield Analysismentioning
confidence: 99%